Analisis Kondisi Moral Remaja yang Bermain Judi Online di Desa Dolok Sagala - Qomariah, Laili; Abdurraman, Zulkarnain (Kamaya: Jurnal Ilmu Agama, 2024)
The background to this research is the viral online gambling that occurs in society, especially among teenagers in Dolok Sagala Village. There are many losses caused to online gamblers. The aim of this research is to analyze the moral condition of teenagers who play online gambling in Dolok Sagala Village regarding the impacts caused by playing online gambling, namely that it can harm themselves and others. The research method used is qualitative with a case study approach by conducting an interview with a teenager to be used as a research subject by exploring sources related to the moral condition of teenagers who are online gamblers in Dolok Sagala Village. Deviant behavior such as online gambling can be found in people's lives and is usually carried out by teenagers. Initially, teenagers played online gambling out of curiosity but ended up being addicted to the point that it was difficult to give up because playing online gambling can make money from the winnings they get. The results of this research relate to the moral condition of teenagers who play online gambling which has impacts in terms of material, social and mental and spiritual health. The material impact is that perpetrators who are already dependent on online gambling spend more of their money by committing theft to get more money. The social and mental health impact is an attitude of indifference to the surrounding environment because they prefer to focus on online gambling, which results in stress and depression when they experience defeat and have to earn more money to be able to play again. The spiritual impact is that someone who is addicted to online gambling tends to abandon their religious practices such as praying, fasting, disobeying their parents' orders and lying because of the impact of playing online gambling.